Hemichannels contribute to mitochondrial Ca2+ and morphology alterations evoked by ethanol in astrocytes - Alvear, Tanhia F.; Farias-Pasten, Arantza; Vergara, Sergio A.; Prieto-Villalobos, Juan; Silva-Contreras, Antonia; Fuenzalida, Fernando A.; Quintanilla, Rodrigo A.; Orellana, Juan A. (Frontiers in Cell and Developmental Biology, 2024)
Alcohol, a toxic and psychoactive substance with addictive properties, severely impacts life quality, leading to significant health, societal, and economic consequences. Its rapid passage across the blood-brain barrier directly affects different brain cells, including astrocytes. Our recent findings revealed the involvement of pannexin-1 (Panx1) and connexin-43 (Cx43) hemichannels in ethanol-induced astrocyte dysfunction and death. However, whether ethanol influences mitochondrial function and morphology in astrocytes, and the potential role of hemichannels in this process remains poorly understood. Here, we found that ethanol reduced basal mitochondrial Ca2+ but exacerbated thapsigargin-induced mitochondrial Ca2+ dynamics in a concentration-dependent manner, as evidenced by Rhod-2 time-lapse recordings. Similarly, ethanol-treated astrocytes displayed increased mitochondrial superoxide production, as indicated by MitoSox labeling. These effects coincided with reduced mitochondrial membrane potential and increased mitochondrial fragmentation, as determined by MitoRed CMXRos and MitoGreen quantification, respectively. Crucially, inhibiting both Cx43 and Panx1 hemichannels effectively prevented all ethanol-induced mitochondrial abnormalities in astrocytes. We speculate that exacerbated hemichannel activity evoked by ethanol may impair intracellular Ca2+ homeostasis, stressing mitochondrial Ca2+ with potentially damaging consequences for mitochondrial fusion and fission dynamics and astroglial bioenergetics.